Penyalahgunaan Data Pribadi Konsumen dalam Perjanjian Digital Berdasarkan KUHPerdata dan Undang-Undang Perlindungan Data Pribadi - Simanjuntak, Fhlorida Agustina; Anjawai, Namrysilia Buti; Permatasari, Rika; Rachmadhanto, Dimas Adam Satrio (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The development of information technology has driven a major transformation in people's transaction patterns from direct interaction to a digital ecosystem that includes e-commerce, financial services, healthcare, education, and government administration. In the midst of the growth of the digital economy, consumers' personal data is developing into a strategic asset that is collected, analyzed, and utilized through big data and artificial intelligence for business purposes. The phenomenon of supervision-based economics raises new risks in the form of data misuse, weak security systems, and inequality in bargaining positions between consumers and business actors. Low digital literacy and complexity of service approvals also increase these vulnerabilities. Although various regulations have been present, including in Indonesia, the effectiveness of protection is still hampered by weak law enforcement, sub- optimal supervision, and the rapid development of digital business models. Therefore, strengthening personal data protection through regulatory harmonization, increasing platform accountability, and public education is an important step to maintain a balance between the growth of the digital economy and the protection of consumer privacy rights.